SARS‐CoV‐2: Mechanism of infection and emerging technologies for future prospects. (16th September 2020) - Li, Shiqin; Li, Sijia; Disoma, Cyrollah; Zheng, Rong; Zhou, Mei; Razzaq, Aroona; Liu, Pinjia; Zhou, Yuzheng; Dong, Zijun; Du, Ashuai; Peng, Jian; Hu, Liqiang; et al.
Abstract: The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has spread globally to over 200 countries with more than 23 million confirmed cases and at least 800, 000 fatalities as of 23 August 2020. Declared a pandemic on March 11 by World Health Organization, the disease caused by SARS‐CoV‐2 infection, called coronavirus disease 2019 (COVID‐19), has become a global public health crisis that challenged all national healthcare systems. This review summarized the current knowledge about virologic and pathogenic characteristics of SARS‐CoV‐2 with emphasis on potential immunomodulatory mechanism and drug development. With multiple emerging technologies and cross‐disciplinary approaches proving to be crucial in our global response against COVID‐19, the application of PROteolysis TArgeting Chimeras strategy, CRISPR‐Cas9 gene editing technology, and Single‐Nucleotide‐Specific Programmable Riboregulators technology in developing antiviral drugs and detecting infectious diseases are proposed here. We also discussed the available but still limited epidemiology of COVID‐19 as well as the ongoing efforts on vaccine development. In brief, we conducted an in‐depth analysis of the pathogenesis of SARS‐CoV‐2 and reviewed the therapeutic options for COVID‐19. We also proposed key research directions in the future that may help uncover more underlying molecular mechanisms governing the pathology of COVID‐19.